Analisis Masalah Guru dan Siswa terhadap Perangkat Pembelajaran Biologi Berbasis Group Investigation untuk Meningkatkan Kemampuan Berpikir Kritis Siswa - Wa Suriati; ELSJE THEODORA MAASAWET; SONJA V.T. LUMOWA (Universitas Sebelas Maret, 2018)
AbstractThe purpose of this research is to obtain 1) the understanding of teachers related to Group Investigation-based biology learning tools and critical thinking skills, 2) description of students' ability in critical thinking, 3) solutions to solve teacher and student problems related to group invetigation-based learning. Understanding of teachers and students obtained by interview and questionnaire is analyzed descriptively qualitative. The result of this research are: 1) the understanding of biology teacher related to biology learning device based on group investigation is still less so less optimal learning process, 2) biology teacher still experiencing difficulties in developing learning device so that require socialization, 3) critical thinking of student in learning still less , 4) the need for direction and guidance to develop learning tools. The sample observations in this analysis were teachers and students at SMAN 6 PPU. The results showed that 78.15% of teachers experienced difficulties in developing learning tools. Teacher states that the students in the class less critical thinking by 70.10%.Keyword: